Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s11269-016-1495-3
|View full text |Cite
|
Sign up to set email alerts
|

Ownership and Performance in Water Services Revisited: Does Private Management Really Outperform Public?

Abstract: Since the late 1970s, water services have been privatised in some developed countries in an attempt to improve performance. However, after three decades of privatisations the superiority of private management is being questioned and several cities are returning to public provision. In this paper we revisit the relationship between ownership and performance in urban water services management using directional distance functions, metafrontiers and Data Envelopment Analysis techniques. The performance in the prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 83 publications
(52 reference statements)
0
30
0
Order By: Relevance
“…One of the forces of change that affects water management and therefore explains governance is the interaction between the public and private entities in charge of resource management [19]. Water is a resource that must respond to vital economic, social and environmental needs; it requires a strong initial capital investment and involves high maintenance costs [24]. Therefore, alternation between public and private water management has been the centre of debate in the water sector, especially regarding the best option to prevent the collapse of the system and achieve efficient distribution of the resource that guarantees the needs of the population are met.…”
Section: Water Governance Public Versus Private Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the forces of change that affects water management and therefore explains governance is the interaction between the public and private entities in charge of resource management [19]. Water is a resource that must respond to vital economic, social and environmental needs; it requires a strong initial capital investment and involves high maintenance costs [24]. Therefore, alternation between public and private water management has been the centre of debate in the water sector, especially regarding the best option to prevent the collapse of the system and achieve efficient distribution of the resource that guarantees the needs of the population are met.…”
Section: Water Governance Public Versus Private Managementmentioning
confidence: 99%
“…Throughout the history of urban water supply, public management has been the most common form of administration [25]. However, the wave of industrial deregulation that took place during the 1970s in the English-speaking world [24] and during the 1980s in the United States [25] encouraged the private sector to increase its participation in water management, a common practice in many developed countries today. For example, taking data from 2007, the private sector supplied water to more than 70% of the population in France and the United Kingdom; between 50 and 70% in the Czech Republic; and between 30 and 50% in Greece, Italy and Spain [26].…”
Section: Water Governance Public Versus Private Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Lots of literature has investigated the impact of private sector participation on the performance of utilities, but the conclusions are diverse. Some empirical studies found that private sector participation improved performance regarding a range of indicators, such as quality of services, productivity, and labor management [3][4][5][6][7][8]. However, other studies found that GOUs were superior with higher technical efficiency [9] or better financial shape and more investments [10].…”
Section: Introductionmentioning
confidence: 99%
“…A few of those studies that claimed private operators to be more efficient also pointed out that GOUs seemed to be less debt-dependent [11]. Nevertheless, Suárez-Varela et al [5] summarized that a large volume of empirical studies, such as Hon et al [12] and Estache et al [13], found little correlation between the ownership and efficiency in the provision of water services. Given these, while there was…”
Section: Introductionmentioning
confidence: 99%